Report on Minor Irrigation Works (West Bengal) - Planning Commission (Planning Commission, 1963)
West Bengal is the only State in India, which borders Himalayas in the north and sea in the south. Many rivers traverse the State. The northern portion of the State is drained by the Tista, the Amo and other hill streams, which join the Brahmputra. Rivers emerging from the western hills in Santhal Parganas, Bihar and Chhota Nagpur flow through the south-western region of the State. The great Ganga and many of its spill-channels pass through its central plains and fan out into the fertile deltaic areas. Physical Regions—According to physical configuration and topographical features of the land, the State can be divided into four distinct regions:— (a) First is the South Western region consisting of the districts of Birbhum, Burdwan, Bankura and Midnapore, the western parts of Hooghly and Howrah districts, and the valleys of the Damodar, the Ajoy, the More, the Dwarkeshwari, the Kasai and the Silai rivers. The soils mostly consist of laterite and sandy loams.
Report on Minor Irrigation Works
Committee on Plan Projects, New Delhi